Efficacy of systemic propranolol for severe infantile haemangioma of the orbit and eyelid: a case study of eight patients. Issue 3 (14th June 2011) - Thoumazet, F; Léauté-Labrèze, C; Colin, J; Mortemousque, B
Abstract : Aim: To assess the efficacy of systemic propranolol for severe capillary haemangiomas involving eyelid and orbit. Method: This was a longitudinal retrospective study that began in November 2007, involving eight children with disfiguring orbit and eyelid capillary haemangioma who received oral propranolol therapy. Three patients with life-threatening haemangiomas spreading to the orbit were first treated with systemic corticosteroids and beta-adrenergenic blocking agents. The remaining five patients with functional visual impairment received propranolol only. All children were given propranolol at a dose of 2 mg/kg body weight per day. The treatment was initiated between 2 and 36 months of age, with a follow-up period ranging from 6 to 30 months. Beta-blocking agents were used for 3–10 months. Results: We observed a successful 100% regression: that is, clinical regression by flattening 24 h after the start of treatment, regression on colour Doppler ultrasound imaging with an increase in resistance index of blood vessels, or regression seen on MRI. No re-growth was observed after the trial ended. Conclusion: Despite their self-limiting course, infantile orbital and eyelid haemangiomas can cause visual impairment or disfigurement. Corticosteroids are used as first-line therapeutic agents for problematic infantile haemangiomas. Other options include interferon-α and vincristine, which present problematic side effects. In our series, propranolol was shown to inhibit haemangioma tumour growth with a better benefit/risk ratio. In the absence of any randomised study comparing the effects of systemic corticosteroids and propranolol, we propose that beta-blockers could be used as first-line therapy for severe periocular haemangiomas.